Wacode “Wates Coco Delight” & VCO “Virgin Coconut Oil”: Innovation Coconut Products - Nindyawati, Eliza; Salsabila, Rizki Kurnia; Siswahyudi, Jodi; Puspitasari, Ririn Dwi; Putri, Devi Kartika; Mashudi, Sugeng (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2024)
As an ecotourism village, Wates needs to take strategic steps to maximize its potential and attractions and maintain environmental sustainability. One way is to empower local communities through ecotourism management training and how to maximize the potential of coconut as a superior village product. This study aims to identify and develop the potential of coconut in Wates Village into creative and economical products, namely "Wates Coco Delight" and Virgin Coconut Oil (VCO). Using a participatory action research method involving 50 heads of families in Wates, this study utilized qualitative and quantitative approaches. Data were collected through interviews, observations, and questionnaires, then analyzed using descriptive analysis and simple statistics. The results showed that the use of coconut can increase village income by 40% in one year. The "Wates Coco Delight" and VCO products have proven to be innovations that are well received by local and regional markets, with sales reaching 500 units per month. In conclusion, the development of coconut-based products not only improves the local economy but also strengthens the cultural identity of the village. Thus, Wates Village can be a model for an ecotourism village based on local products. This study makes an important contribution to education and economic empowerment of village communities through sustainable natural resource management.